Neutralization dynamics of slow highly charged ions passing through graphene nanoflakes: An embedding self‐energy approach. Issue 2 (27th August 2021) - Balzer, Karsten; Bonitz, Michael
Abstract: We study the time‐dependent neutralization of a slow highly charged ion that penetrates a hexagonal hollow‐centred graphene nanoflake. To compute the ultrafast charge transfer dynamics, we apply an effective Hubbard nanocluster model and use the method of nonequilibrium Green functions in conjunction with an embedding self‐energy scheme, which allows one to follow the temporal changes of the number of electrons in the nanoflake. We perform extensive simulations of the charge transfer dynamics for a broad range of ion charge states and impact velocities. The results are used to put forward a simple semi‐analytical model of the neutralization dynamics that is in very good agreement with transmission experiments, in which highly charged xenon ions pass through sheets of single‐layer graphene.